The Effect Of Self-Etch And Total-Etch Bonding Systems Application On Microleakage Of Bulkfill Flowable Composite Restoration In Carbonated Drink Immersion - Widya Saraswati; Auryn Thania Song Hadinata; Sukaton Sukaton (Conservative Dentistry Journal, 2019)
Background: Resin composite is more advanced today, but the marginal leakage still can not be avoided, for it takes the bonding system. Bonding system aims to provide a layer between a substrate and composite so it has a strong bond . The current latest bonding system is called universal bonding. It can be used with 2 techniques, both self etch and total etch. Universal bonding contains 10MDP so there’s no need for etching and priming. 10MDP results in better adhesion than previous bonding monomers  generation. A total etch technique  require a pre-etching step to remove smear layer so that it formed porous as a retentive sites. Purpose : Distinguish the marginal leakage of flowablebulkfill composite overlays with the application of total etch and self etch bonding systems accompanied by immersion of carbonated beverages . Method: Tooth samples were prepared to a depth of 2mm, then the bonding agent was applied directly to the cavity without etching (self etch), etched before the application of bonding agent (total etch ), directly loaded without pre-etching and bonding (control) . using a flowablebulkfill composite as a material restorative. All of the sample both total etch and self-etch  soaked in Cola drinks for 5 minutes then repeated until 10 treatment each day (one day is assumed to be 12 hours) up to 7 days, followed by immersion in the methylene blue 0.5 % for 24 hours . Sample then splittedbuccolingual direction, leakage was assessed by scoring the edge trough the depth of methylene blue penetration.  Result:  Mann-Whitney Test showed a significant differences (P>0.05 ) each group . Conclusion: Marginal leakage of composite restoration with total etch technique and self etch technique is smaller than the control group, and the marginal leakage of composite restoration with total etch technique is smaller than that of self etch group .